Triglyceride-glucose index: carotid intima-media thickness and cardiovascular risk in a European population - Chiara Pavanello; Massimiliano Ruscica; Sofia Castiglione; Giuliana Germana Mombelli; Antonia Alberti; Laura Calabresi; Cesare Riccardo Sirtori (Cardiovascular Diabetology)
Abstract Background The triglyceride-glucose (TyG) index is now widely recognized as a marker of insulin resistance and has been linked to the development and prognosis of atherosclerotic cardiovascular diseases (ASCVD) in numerous populations, particularly in the Eastern world. Although there are fewer reports from the Western world, and they are sometimes contradictory, the absence of definitive data on the relationship between a raised TyG index and cardiovascular risk suggested the opportunity of testing this biochemical marker against a well-established vascular marker such as the carotid intima media thickness (c-IMT). Methods Primary prevention patients were selected from a cohort of individuals who underwent c-IMT measurement between 1984 and 2018 at the Dyslipidemia Center at the ASST Grande Ospedale Metropolitano Niguarda in Milan, Italy. The TyG index was calculated as the Ln [fasting TG (mg/dL)×fasting glucose (mg/dL)/2]. Carotid ultrasonography was performed using echographic measurements of the far walls of the left and right common, internal carotids, and bifurcations. Patients were followed for up to 20 years with periodic evaluation of biochemical parameters. ASCVD events were monitored through hospital records, where all patients were regularly examined. Results The analysis included 3108 individuals with a mean age of 54.9 ± 13.1 years. Participants were generally non-obese, with an average BMI of 24.6 ± 3.5 Kg/m2. Among the women, 83.1% were postmenopausal. The mean TyG index was 8.65 ± 0.59. There was a significant association between the TyG index and all c-IMT measurements. Those in the highest TyG index quartiles had significantly higher IMTmean and IMTmax compared to those in the lower quartiles. These associations were consistent across all vascular sites examined and remained significant after adjusting for all potential confounders. Kaplan-Meier survival analysis revealed an increased incidence of ASCVD events in the two highest TyG index quartiles. Conclusions TyG index is a sensitive marker of risk in a European population with moderate ASCVD risk, as assessed by c-IMT measurements, in a large cohort of Lipid Clinic patients.